Incidence of the genetic mutations in patients with coronary artery disease - Ekim, Meral; Ekim, Hasan (The European Research Journal, 2017)
Objectives. Coronary artery disease (CAD) is the leading cause of mortality in the world. It is a complex disorder resulting from the interaction between environmental risk factors and hereditary predisposition. The role of the factor V Leiden (FVL), protrombin gene (PT G20210A) and methylenetetrahydrofolate reductase (MTHFR) C677T polymorphisms in the development of CAD is controversial. In this study, we investigated the incidence of these polymorphisms in order to delineate their roles in the development of CAD in a tertiary University hospital. Methods. This study included 58 consecutive CAD patients. Diabetic and hypertensive patients were excluded. FVL, PT G20210A, and MTHFR (C677T, A1298C) mutations were investigated in all patients. Polymerase chain reaction and the amplification refractory mutation system were used to identify these polymorphisms. Results. Thirty-six men and 22 women were enrolled with an age ranging between 41 to 85 (mean age: 62.75±9.18 years). The heterozygous PT G20210A genotype was identified in 5 (8.6%) patients (2 males, 3 females). The heterozygous FVL genotype was found in 8 (13.8%) patients (6 males and 2 females). The incidence of homozygous MTHFR C677T and homozygous MTHFR A1298 carriers was found to be 17.2% and 8.6%, respectively. There were no significant differences in the distribution of polymorphisms according to gender (p>0.05). Conclusions. The FVL and PT G20210A polymorphisms most likely play a contributory role in the development of CAD. In contrast, the MTHFR C677T and MTHFR A1298C genotypes were not associated with a predisposition to the development of CAD. However, in compound MTHFR C677T/A1298C carriers, the presence of FVL or PT G20210 polymorphism may contribute the development of CAD. Further studies are needed to support these findings.